CORPORATE GOVERNANCE IN THE AGE OF GENERATIVE AI A LEGAL PERSPECTIVE - Naili, Yuris Tri; Purwono, Purwono (LPPM Universitas Trunojoyo Madura, 2024)
The emergence of Artificial Intelligence (AI) technology has brought significant changes to corporate governance, presenting various opportunities and challenges. The implementation of AI in corporate governance can have a significant impact on the level of governance and create conditions that support better decision-making. However, the use of AI also has negative impacts such as data privacy violations, gender discrimination, reputational loss, and compliance issues. Additionally, there are legal challenges in the application of AI, including the legality of data utilization, accountability, fairness, transparency, security, and data privacy. Through a systematic literature review, including the analysis of articles, legal documents, and relevant regulations, this study aims to analyze the impact of Generative AI on corporate governance, identify potential legal challenges, and investigate relevant legal perspectives in addressing these challenges